Association of fracture configuration and callus formation with a concentration of proinflammatory cytokines in children with long bone fractures - Paunović, Zoran; Milutinović, Sanja; Stanković, Nikola; Abazović, Džihan; Stanojević, Ivan; Rakić, Mia; Djukić, Mirjana; Šupić, Gordana; Vojvodić, Danilo; Marić, Dušan; Khan, Wasim S; Starčević, Srdjan (Vojnosanitetski pregled, 2021)
Background/Aim. The inflammatory response is of utmost importance in bone healing, but the precise role of cells and cytokines remains unclear. In our study, we examined the association between interleukin-1β (IL-1β), tumor necrosis factors alpha (TNF-α), monocyte chemoattractant protein-1 (MCP-1) and interleukin-8 (IL-8) concentrations, fracture configuration, and callus formation. Methods. Serum cytokine concentrations were determined in 78 non-obese children with long bone fractures (group 1), 10 children with finger fractures (group 2), and 10 healthy controls (group 3). Blood samples were taken immediately after fracture upon hospital admission for groups 1 and 2. Differences in cytokine concentrations were analyzed among groups and categorized according to fracture configuration and callus formation. Results. IL-1β and TNF-α levels were lower in patients that went on to produce incomplete callus compared with patients that formed complete callus. Surprisingly, the average IL-1β concentration was highest in the healthy control group. The only significant correlation between IL-1β and TNF-α was in the group with moderate callus formation. MCP-1 level was slightly increased in all patient groups compared to controls, with no mutual difference. An average IL-8 level showed a clear decrease tendency from the group with incompletely formed callus toward the group with completely formed callus compared to controls, without significant difference. Children with epiphysiolysis had the lowest concentrations of cytokines compared with all other fracture types including transverse, oblique, and spiral. There were significantly lower concentrations of IL-1β and MCP-1 in patients with less fragment displacement compared with patients with greater fragment displacement. Conclusion. The systemic inflammatory response is important in physiological bone healing. High early production of IL-1β, TNF-α, and MCP-1 is associated with greater callus formation and better healing outcome, while increased IL-8 level is associated with poor callus formation and worse healing outcome. Our results indicate that epiphysiolysis and larger fragment displacement are associated with delayed fracture healing.
Keywords: prelomi; prelomi, zarastanje; deca; adolescenti; kalus; interleukin-1beta; faktor nekroze tumora-alfa; monocitni hemoatraktantni protein-1; interleukin-8; prognoza